1991
DOI: 10.1021/jm00112a035
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective adenosine A2 receptor agonists in a series of N-alkylated 2-aminoadenosines

Abstract: A wide variety of 2-substituted aminoadenosines were prepared for comparison with the moderately A2 receptor selective adenosine agonist 2-anilinoadenosine (CV-1808). High selectivity combined with significant affinity at the A2 receptor in rat membranes was observed for those amines bearing a two-carbon chain to which was attached an aryl, heteroaryl, or alicyclic moiety. 2-(2-Phenethylamino)adenosine (3d), a 14-fold A2 selective compound, was modified by introduction of a variety of substituents in the benze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…Studies of the dependence of potency on the size of the ring in N6-cycloalkyl substituted analogs identified CHA and CPA as particularly potent and A,-selective (280-and 780-fold, respecti~ely).~7 Subsequent studies showed that N6-bicycloalkyladenosines are even more A, selective, with the lR, 2S, 4s isomer of N6-(2-endo-norborny1)adenosine(S-ENBA, 4) being 4700-fold selective, while its 5'-C1 analog is even 16,000-fold selective for the A, receptor.48 The N6-region is essentially hydrophobic in nature, and may accommodate very large substituents. Hydrophilic 58 Further structural modifications at the 2-position led to development of 2-alkoxyaden~sines,~~ e.g., CHEA (27; A,: 22nM; A,: 1580 nM),60 2-aralkoxyadenosine derivatives,61 such as MPEA (28; A,: 11 nM; A,: 49 nM),60 as well as 2-alkynyladenosines . 62 For example, the 2-alkynyl derivatives 2-hexynyladenosine (2-HNA, 29) and 2-octynyladenosine (2-ONA, 30) are potent A, agonists (K, values 4 and 12 nM) with 36-and 17-fold selectivity, respectively, for the A, receptor in binding assays.…”
Section: Adenosine Derivatives As Adenosine Agonistsmentioning
confidence: 99%
“…Studies of the dependence of potency on the size of the ring in N6-cycloalkyl substituted analogs identified CHA and CPA as particularly potent and A,-selective (280-and 780-fold, respecti~ely).~7 Subsequent studies showed that N6-bicycloalkyladenosines are even more A, selective, with the lR, 2S, 4s isomer of N6-(2-endo-norborny1)adenosine(S-ENBA, 4) being 4700-fold selective, while its 5'-C1 analog is even 16,000-fold selective for the A, receptor.48 The N6-region is essentially hydrophobic in nature, and may accommodate very large substituents. Hydrophilic 58 Further structural modifications at the 2-position led to development of 2-alkoxyaden~sines,~~ e.g., CHEA (27; A,: 22nM; A,: 1580 nM),60 2-aralkoxyadenosine derivatives,61 such as MPEA (28; A,: 11 nM; A,: 49 nM),60 as well as 2-alkynyladenosines . 62 For example, the 2-alkynyl derivatives 2-hexynyladenosine (2-HNA, 29) and 2-octynyladenosine (2-ONA, 30) are potent A, agonists (K, values 4 and 12 nM) with 36-and 17-fold selectivity, respectively, for the A, receptor in binding assays.…”
Section: Adenosine Derivatives As Adenosine Agonistsmentioning
confidence: 99%
“…Be cause the guinea pig was the species for the physiological preparations and the rat the spe cies for the biochemical preparations, a few of the 2-substituted adenosines were compared in heart preparations and in brain binding assays for both guinea pig and rats [41], Spe cies differences were present, but they were not of a magnitude or diversity that negated the present cross-species comparison of activ ities in rat biochemical preparations with ac tivities previously found for guinea pig physi ological preparations. Recently, a series of 2-alkylamino-and 2-aralkylaminoadenosines were reported, many of which were selective for A: receptors [42].…”
mentioning
confidence: 99%
“…From the whole series, which includes 2-amino-, [80] 2-hydrazino-, [32,45,81] 2-alkoxy-, [82] 2-alkylthio-, [83][84][85] and 2-alkynyl-derivatives, [37,38,77,79] the compounds showing the highest A 2A affinity bore a phenylethyl (or cyclohexylethyl) group directly linked to the heteroatom or triple bond (see Table 1 compounds 4-9).…”
Section: -Substituted Adenosine Derivativesmentioning
confidence: 99%